2018
DOI: 10.1177/1471301218762838
|View full text |Cite
|
Sign up to set email alerts
|

Independence, loss, and social identity: Perspectives on driving cessation and dementia

Abstract: The purpose of this study on driving cessation was to explore the process of coping, decision-making and adaptation through this major life transition. We sought to examine understandings of the emotional responses of drivers and ex-drivers with dementia from the perspective of healthcare providers and family caregivers of persons with dementia. Interviews and focus groups were conducted with several key informant groups: healthcare providers who work with patients with dementia and their families ( N = 10), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…As with any loss, driving cessation may elicit a grief reaction, amplified by the potential changes in independence, status and social interaction 22 33. While GPs are well placed to guide and offer compassionate support to patients through these adjustments,35 we found that their current efforts seem to fall short of patients’ expectations; patient participants requested more empathy and acknowledgement for the impact of driving cessation on their quality of life.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As with any loss, driving cessation may elicit a grief reaction, amplified by the potential changes in independence, status and social interaction 22 33. While GPs are well placed to guide and offer compassionate support to patients through these adjustments,35 we found that their current efforts seem to fall short of patients’ expectations; patient participants requested more empathy and acknowledgement for the impact of driving cessation on their quality of life.…”
Section: Discussionmentioning
confidence: 83%
“…Findings include GPs’ view of themselves as reluctant regulators13 who ‘hate’ that driving assessment has anything to do with their role,14 15 and frequent uncertainty about their legal and ethical obligations 16–21. Evaluations of patients’ responses to the prospect of driving cessation in the context of cognitive impairment highlight a range of negative emotions, such as anger, frustration and sadness, the disruption to self-identity and fear of loss of independence 22 23. Up to one-fifth of GPs report a patient leaving their practice because of FtD consultations that have gone badly, highlighting just how distressing these consultations can be for patients 21…”
Section: Introductionmentioning
confidence: 99%
“…Ability to drive is a primary focus of transportation research in the United States, with the main focus on safety issues related to decline in functional, visual, and cognitive status as people age, risk factors for driving cessation, and the transition to nondriving status (Bird et al, 2017; Dickerson, Meuel, Ridenour, & Cooper, 2014; Ross, Freed, Edwards, Phillips, & Ball, 2017; Vivoda, Heeringa, Schulz, Grengs, & Connell, 2017). As the predominant form of daily transportation in the United States, driving fulfills a variety of needs for older adults, such as facilitating social engagement and a need for independence and self-identity, as well as practical needs such as shopping and medical appointments (Chihuri et al, 2016; Sanford et al, 2018). There is also growing interest in expanding access to alternative transportation for older adults such as paratransit services, specialized transportation and shuttle services, and on-demand ride-share services such as Uber (Chaiyachati et al, 2018; Dickerson, Molnar, Bedard, Eby, Berg-Weger, et al, 2019a; MacLeod et al, 2015; Vivoda, Harmon, Babulal, & Zikmund-Fisher, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has identified health factors that increase the risk for driving restriction or cessation, including cognitive impairment, vision loss, diabetes, and heart failure (Croston, Meuser, Berg-Weger, Grant, & Carr, 2009; Dugan & Lee, 2013; Keay et al, 2009; Kowalski et al, 2012; Seiler et al, 2012; Sims et al, 2011; van Landingham et al, 2013). Driving cessation represents a significant life transition that challenges social participation and preservation of self-identity (Sanford et al, 2018). In addition, driving cessation is linked to an increased risk of depression and nursing home admission (Chihuri et al, 2016; Fonda, Wallace, & Herzog, 2001; Freeman, Gange, Munoz, & West, 2006; Ragland, Satariano, & MacLeod, 2005; Windsor, Anstey, Butterworth, Luszcz, & Andrews, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation